The jointed-veined rock mass characterization approach - benchmarking for caveability, fragmentation, and ground stability decision making - Brzovic, A; Roy, J; Otto, S; Rogers, S; Bewick, R; Griffiths, C; Martin, J; Mah, R (MassMin 2024: 9th International Conference & Exhibition on Mass Mining, 2024)
Caveability, fragmentation, and ground stability are important aspects impacting production reliability in a caving mine and can be fatal flaws if they are not properly assessed. In addition, there is evidence from historical and current caving mines that revenue recovery loss has occurred due to production disruption from these aspects. The root cause of the unreliable forecasts is often due to failure of rock mass characterizations to accurately determine the key factors controlling rock mass behaviour. A data collection and analysis approach has been developed using a jointed-veined rock mass matrix (previously reported). The overall methodology has been applied to several cases to identify potential challenges and make decisions about caveability, fragmentation, and excavation stability at early stages of a project or mine design implementation. The nature of most caving ore bodies are such that alteration, vein systems, and faults are the main characteristics of the rock mass. The approach relies on borehole geotechnical and geophysics data, laboratory strength testing, and point load index testing that target both the intact rock and veins. Data analysis includes DFN modelling to classify rock masses according to the intensity of both open structures and potential block forming veins using P32 (a nondirectional volumetric intensity parameter). Block modelling of P32 and rock strength is completed to understand spatial variability of characteristics and define geotechnical domains. In this paper, data from various caving operations and projects, as represented in the jointed-veined matrix, are presented to document examples of rock mass characteristics across different orebody classes.